Under representation of people with epilepsy and intellectual disability in research. - Rohit Shankar; Charles Rowe; Alje Van Hoorn; William Henley; Richard Laugharne; David Cox; Raj Pande; Ashok Roy; Josemir W Sander (PLoS ONE)
Purpose One quarter of people with epilepsy have an intellectual disability (ID) and one fifth of people with an ID have epilepsy. Both conditions are associated with higher levels of morbidity, stigma and premature mortality. There have been calls for action to promote more research in this group. We examined if this group are represented adequately in current research. Methods The proportion of research output in epilepsy conferences and publications relevant to ID and the proportion in ID conferences and publications on epilepsy for 2015-2016 were identified. As the percentage of children in the population with epilepsy is 17%, research output of this group was compared with the ID group. Recognised material was classified based on whether it applied to general epilepsy/ID research, children with epilepsy or people with epilepsy and ID. Data was analysed to determine the proportion of presented research specifically identifying people with epilepsy and ID. Results Fewer than 2% of presentations at epilepsy conferences specifically related to the ID and epilepsy group compared to 15% relating to children with epilepsy. Similarly only 1.4% of the research presented at major ID conferences related to those with people with epilepsy and ID. About 5% of published research in the field of epilepsy related to those with ID as compared with 24% for children with epilepsy. Twelve percent of published research in ID specifically identified epilepsy. Conclusion Publications and conference presentations, on the population with epilepsy and comorbid ID is under-represented. Increased research in this area might assist in improving the quality of care for this relatively neglected group.